Monitoring and assessing the amount of particulate matter less than 2.5 microns (PM2.5) in the indoor and outdoor areas: A case study of Udon Thani Rajabhat University (Sam Phrao Education Center) - Meesang, Winai; Baothong, Erawan; ยาบุษดี, Piyavadi; Kitisriworaphan, Wipaporn; Phukongthong, Sivaporn; Somnil, Poosanapas; intrachain, Subchart (Journal of Advanced Development in Engineering and Science, 2023)
This research aimed to assess the amount of particulate matter less than 2.5 microns (PM2.5) in indoor and outdoor areas of Udon Thani Rajabhat University (Sam Phrao Education Center). In the study area, the amount of particulate matter less than 2.5 microns, temperature, and relative humidity were investigated for 8 hours each day, from 8:00 a.m. to 4:00 p.m., 5 consecutive days each week. The period of this study was 1 year from November 2019 to November 2020. The average amount of particulate matter has been reported according to winter, summer, and rainy seasons. The I/O ratios were analyzed, and a mathematical model was designed. The results revealed that the amount of fine particulate matter in indoor the study areas during the winter, the summer, and the rainy seasons were in the range of 59.87 - 133.50 mg/m3, 20.72 - 106.65 mg/m3, and 16.52 - 109.21 mg/m3, respectively. The amount of fine particulate matter in outdoor study areas in the winter, the summer, and the rainy seasons were in the range of 50.71 - 140.11 mg/m3, 29.01 - 42.53 mg/m3, and 16.42 - 116.25 mg/m3, respectively. In winter, the PM2.5 particulate has the highest value because of the low relative humidity and low temperature. In summer, the PM2.5 particulate matter has lower than in the winter because the relative humidity was lower, and the temperature was higher leading to the air circulation on the bottom surface making PM2.5 dust easily moveable. On rainy, the PM2.5 particulate has the lowest due to the higher relative humidity, resulting in a downwash of the dust called wet deposition. The results of the exposure assessment analysis were based on the ratio between indoor and outdoor particulate matter levels revealed that the highest value was 1.40±0.12, indicating that there is a chance of being exposed from inside more than outside of the building. The coefficient of determination obtained from the mathematical model for PM2.5 particulate matter from inside and outside of the building (R2) were 0.85 and 0.97, respectively.